TLR4 and C5aR crosstalk in dendritic cells induces a core regulatory network of RSK2, PI3Kβ, SGK1, and FOXO transcription factors. Issue 4 (1st October 2017) - Zaal, Anouk; Nota, Benjamin; Moore, Kat S.; Dieker, Miranda; van Ham, S. Marieke; ten Brinke, Anja
Abstract : Identification of a central regulatory network formed by FOXO1, FOXO3, RSK2, PI3Kβ 2, and SGK1 upon C5aR and TLR4 crosstalk in human monocyte‐derived DCs. Abstract : Crosstalk between complement component 5a receptors (C5aRs) and TLRs in dendritic cells (DCs) occurs upon pathogen invasion; however, studies on C5aR and TLR crosstalk mainly focused on the modulating effect of C5a on TLR‐induced cytokine production. To elucidate the breadth of C5aR and TLR4 crosstalk, the effect of simultaneous treatment with C5a and LPS was investigated in human monocyte‐derived DCs (moDCs) 2 h after stimulation using whole transcriptome sequencing analysis. Although the effect of C5a on hallmark genes defining TLR4‐induced DC maturation was limited at this time point, RNA sequencing analysis revealed a great variety of novel C5a targets, of which many interfere with TLR4‐mediated immune activation. Analysis of functional relationships among these genes uncovered induction of a central immune regulatory network upon C5aR and TLR4 crosstalk, involving the transcription factors forkhead box (FOX)O1 and FOXO3 and the signaling molecules serum‐ and glucocorticoid‐inducible kinase (SGK1), ribosomal S6 kinase 2 (RSK2), and PI3Kβ. C5aR and TLR crosstalk, furthermore, yielded down‐regulation of mainly proinflammatory network branches, including IL‐12B, IL‐2Rα (IL‐2RA), and jagged 1 (JAG1) and cooperative induction of predominantly anti‐inflammatory network branches, including sphingosine kinase 1 (SPHK1), β2 adrenergic receptor (ADRB2), gastric inhibitory polypeptide receptor (GIPR), and four‐and‐a‐half Lin11, Isl‐1, and Mec‐3 domains protein 2 (FHL2). Together, these data point toward induction of generalized immune regulation of DC function. Motif enrichment analysis indicate a prominent role for basic leucine zipper (bZIP) and IFN regulatory factor 4 (IRF4) transcription factors upon C5aR and TLR4 crosstalk. Additionally, differences were observed in the modulating capacity of C5a on DCs in the absence or presence of a pathogen (TLR stimulus). Our findings shed new light on the depth and complexity of C5aR and TLR4 crosstalk and provide new foci of research for future studies.